2019
DOI: 10.1021/acsanm.9b01693
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Superparamagnetic Nanoparticle-Based Microballoons for Mechanical Force Monitoring by Magnetic Particle Spectroscopy

Abstract: The determination of induced mechanical forces in ball mills is an ongoing problem, which is so far mainly addressed by simulations. Herein, we suggest utilizing superparamagnetic microballoons as sensor particles for mechanical stress. The defined assembly of superparamagnetic nanoparticles yields microballoons with hollow cores, which makes them susceptible to mechanical forces. It is shown that the hollow structure is continuously fragmented under static or dynamic force application. By use of magnetic part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 22 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…In order to understand the great relevance of the approach developed here in terms of code variety, but even more importantly, also towards its application as a magnetic marker technology, one has to at least roughly comprehend the principle of MPS (more thorough explanations are given in the Figure S6, Supporting Information, in original [ 36,41 ] and previous [ 23,37,38 ] publications): the measured voltage, induced by a magnetic sample which is exposed to an AC magnetic field, is fast Fourier transformed (FFT) to obtain the harmonic spectrum. As this representation is spectral, a quantitative description is obtained after normalizing the magnetization amplitude to the maximum intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand the great relevance of the approach developed here in terms of code variety, but even more importantly, also towards its application as a magnetic marker technology, one has to at least roughly comprehend the principle of MPS (more thorough explanations are given in the Figure S6, Supporting Information, in original [ 36,41 ] and previous [ 23,37,38 ] publications): the measured voltage, induced by a magnetic sample which is exposed to an AC magnetic field, is fast Fourier transformed (FFT) to obtain the harmonic spectrum. As this representation is spectral, a quantitative description is obtained after normalizing the magnetization amplitude to the maximum intensity.…”
Section: Resultsmentioning
confidence: 99%
“…This is, as upon agglomeration of magnetic nanoparticles, their close proximity strongly alters their magnetic properties in the utilized setup. [37][38][39] Thus, the hierarchical approach prevents strong coupling of individual nanoparticles [40] and is key to distinguish different compositions by MPS. The different supraparticles can still be easily distinguished after several weeks of storage in ambient conditions, which is essential for a functional marker (see Figure S10, Supporting Information).…”
Section: Adapting the Principle Of A Musical Ensemble To Create An Advanced Magnetic Marker Supraparticlementioning
confidence: 99%
“…Cold chain breach indicating magnetic supraparticulate microrods have been described by Müssig et al. [ 208 ] Besides other mechanical stress indicator SPs, [ 209 ] a shear indicator based on hierarchically structured luminescent dye‐doped silica NPs and iron oxide NPs assembled via spray‐drying has been established. [ 207 ] It reports damages, e.g., by an increase in fluorescence signal (Figure 11c).…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%
“…MPS is a recent magnetic measurement technique which detects the non-linear magnetic behavior of powder or liquid samples as explained in previous publications. [6][7][8]13 Briey, an alternating magnetic eld (AE17 mT) is applied and the time-dependent magnetization of the sample is detected by measuring the induced voltage in pickup coils. Aer fast Fourier transform (FFT), higher harmonics are obtained from the nonlinear magnetization of SPIONs.…”
Section: Magnetic Characterization Of Non-agglomerating Spionsmentioning
confidence: 99%
“…Recent work indicated that magnetic particle spectroscopy (MPS) can sensitively detect changes induced by agglomeration of individual magnetic nanoparticles. [6][7][8] Due to the method's fast measurement speed and easily congurable measurement setup, it is potentially promising to in situ gain a better understanding of dynamically agglomerating magnetic particles in dispersion. 9 With respect to future applications, being able to precisely tailor agglomeration and thus magnetic properties of nanoparticles could be utilized to improve the efficiency of hyperthermia.…”
Section: Introductionmentioning
confidence: 99%